The Effect of Adding BSF (Black Soldier Fly) Maggot Flour in Feed on the Performance of Male Quail - Abdullah, Imron; Risyani, Lusia; Andika Fitroh, Bagus (Bulletin of Applied Animal Research, 2024)
The livestock sub-sector is a sector that has a major contribution to the economy, especially in achieving food security for the Indonesian people. Quail farming has enormous potential to be developed. Maggot BSF is widely used by breeders as a feed ingredient to replace fish meal or as an alternative to additional feed for livestock. This research was conducted on May 24 2023 to July 5 2023, at Gebyok Rt02 Rw05 Ngemplak, Kartosuro District, Sukoharjo Regency, Central Java. The quails used were male, 240 days old, divided into 4 treatments and 6 replications where each replication contained 10 quails. The frequency of feeding was 2 times a day, feed and drinking water were given ad libitum for 6 weeks (42 days). The treatment applied was P0: Basal feed without the addition of BSF maggot flour; P1: Basal feed+5% BSF maggot flour; P2: Basal feed+10% BSF maggot flour; P3: Basal feed+15% BSF maggot flour. The cages used are bateray cages (multilevel), measuring 70cm x 120cm x 60cm in 24 plots. The basal feed used in the study was BR-1 produced by PT Japfa Comfeed Indonesia Tbk. The results of the study were significantly different treatment of feed consumption with the highest score of 12.518 in the 10% administration group. Giving Maggot BSF has no effect on body weight gain. The treatment had no effect on the conversion of male quail feed. Keywords: male quail; BSF, Performance.